Evaluation of the effects of the toilet training process on the child's quality of life - ÖZGÜR, EMRAH GÖKAY (My University, 2023)
Background: Toilet training is a significant developmental milestone for children. During the process of toilet training, voiding and defecation problems may develop, which have a major adverse impact on quality of life. The aim of this study was to assess the process to voiding and defecation problems and evaluate that these issues influenced the children’s' quality of life. Methods: The children included in the study were followed up at the Ankara University School of Medicine, Department of Social Pediatrics. Participants were surveyed via a questionnaire that included sociodemographic features, the toilet training process, and the pediatric quality of life inventory. The results were analyzed using IBM SPSS 11.5. Results: The study included 177 children and their parents. There was no correlation between the parents' age, sociodemographic features and the timing of the start of toilet training. In the children included in the survey, voiding problems were found in 55.6% and defecation problems in 23.6%. Urinary retention during play and nocturnal enuresis were more frequent in the children trained at 25–36 months of age. The self-reported quality of life scores in children with voiding problems and with both voiding and defecation problems were lower than those in children who have not had any problems. Conclusions: Even if the child has been toilet trained, it is essential to investigate daily urination and defecation habits at every follow-up visit, even if just briefly, and to discuss with families when a physician should be consulted.
Keywords: defecation problems; PedsQL; quality of life; toilet training; voiding disorder